A population‐based survey on the influence of the menstrual cycle and the use of hormonal contraceptives on sleep patterns in São Paulo, Brazil. Issue 2 (27th November 2012) - Hachul, Helena; Andersen, Monica L.; Bittencourt, Lia; Santos‐Silva, Rogério; Tufik, Sergio
Abstract: Objective: To investigate the effects of the phases of the menstrual cycle and the use of hormonal contraception on sleep patterns in a population‐based study. Methods: In a prospective study carried out among premenopausal women between July and December 2007, a 3‐stage cluster sampling was used to ensure accurate representation of the general population of São Paulo, Brazil. Questionnaires were administered, hormonal assays were performed, and full‐night polysomnography was recorded. Results: The study sample included 297 premenopausal women. Women in the follicular phase complained of fatigue more than those in the luteal phase and those using hormonal contraceptive treatment. Premenopausal women using hormonal contraceptives had a significantly lower apnea–hypopnea index (1.1 ± 2.0) compared with women in both the follicular (2.2 ± 4.5) and the luteal (2.9 ± 5.4) phases ( P = 0.01). Women taking hormonal contraceptives tended to have increased sleep efficiency compared with women in either the follicular or luteal phases. Conclusion: The use of hormonal contraceptives was associated with a lower apnea–hypopnea index and a trend toward improved sleep efficiency. The current findings suggest that the use of hormonal contraceptives has a stronger association with sleep duration compared with menstrual cycle phase.